Effectiveness of the Implementation of Local Government Information Systems in Financial Administration - Dasni, Dasni; Abidin, Zainul; Ramadhan, Syahril (Universitas Medan Area, 2025)
This study aims to explain the effectiveness of implementing local government information systems in financial administration at the Baubau City DPRD Secretariat. This study uses a descriptive method with a qualitative approach. Data was collected through interviews, observations, and documentation and analyzed by reducing the presentation and conclusion. The study results show that the implementation of SIPD in the Baubau City DPRD Secretariat effectively understands the program, the accuracy of the targets, the timeliness, and the achievement of goals. The transparency resulting from implementing SIPD strengthens financial accountability, reduces the potential for corruption, and makes the reporting process more efficient. However, it is necessary to increase the capacity of human resources, improve infrastructure, and strengthen coordination between the agencies involved to overcome delays and errors in input and reporting and improve the effectiveness of the overall implementation of SIPD.